Psychosocial support to HIV positive mothers in Malaysia primary care clinics - Abdullah, Fa’iza (2015)
Overview HIV/AIDS HIV disease affecting 16,000 people each day ~ 40 million PLHA worldwide: 17.6 million are women and 2.7 million are children < 15 years old Total number of HIV positive until 2010 > 90,000 cases > 13,000 cases - death related from AIDS disease.